Situation Report: Poland, 23 February 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. "Year of Polish Science and Humanities" Social Program of the Ministry of Labor, Wages, and Social Affairs Friendship Visit to Syria Trade Protocol for 1973 Socialist Youth Union Congress Trade Union Plenum on Youth Polemic at Helsinki Talks